Casting a net to better understand fisheries management: An affiliation network analysis of the Great Lakes Fishery Commission. (July 2015) - Mulvaney, Kate K.; Lee, Seungyoon; Höök, Tomas O.; Prokopy, Linda S.
Abstract: Natural resource governance, and fisheries management in particular, includes multiple governmental jurisdictions and stakeholders. For many fisheries, however, an understanding of the numbers of organizations involved in management and the relationships among those organizations remains lacking. Using an email survey, we investigated the affiliation network of formal and informal relationships of Great Lakes Fishery Commission (GLFC) policy and decision makers (i.e., organizations involved in the management of Laurentian Great Lakes fisheries). The 63 respondents identified 1516 relationships with 149 organizations which provide numerous opportunities for groups to share resources and information. Important organizational roles that can be identified through network analysis include the coordinating role of the GLFC׳s staff and connections through stakeholder representatives. Informal relationships are an important aspect of the affiliation network with more than one-third of all relationships identified as informal relationships and 16 organizations identified only through informal relationships. Identification of affiliation networks could be a useful tool for understanding the connection between diverse stakeholder organizations and natural resource managers. Highlights: The affiliation network of the Great Lakes Fishery Commission is highly complex. 1516 ties were identified between the GLFC and 149 organizations. Both formal and informal relationships are important in the affiliation network. Different management and stakeholders contribute different roles to the GLFC network. Sportfishing and commercial fishing organizations are important bridges. The GLFC and state and federal agencies are important coordinating participants.